Serum Vitamin D Levels and Their Association with Periodontal Parameters in Periodontitis Patients from Northeastern Peninsular Malaysia (Bangladesh Journal of Medical Science, 2026)
Background Vitamin D plays a significant role in modulating immune system, inflammatory processes, and bone metabolism. Vitamin D deficiency has been proposed as a risk factor for periodontitis. However, the association between vitamin D levels and periodontitis remains inconclusive. Objective: The aim of this study was to determine the serum vitamin D levels in periodontitis patients from the northeastern Peninsular Malaysia and to assess its association with periodontal parameters. Methodology A cross-sectional study was conducted among 43 participants, comprising 20 periodontitis patients and 23 healthy controls. Periodontal parameters were assessed, including plaque score, gingivitis score and periodontal pocket depth. Blood samples were collected and analyzed for serum vitamin D levels using an automated COBAS 6000 analyser. Results The mean age of periodontitis patients and healthy controls was 41 ± 13 and 35 ± 14 years, respectively. Both groups exhibited low mean serum vitamin D levels: 20.48 ± 4.1 ng/mL in the periodontitis group and 20.99 ± 3.9 ng/mL in the healthy group, with no statistically significant difference (p > 0.05). Approximately 50% of periodontitis patients were vitamin D deficient (